Synthesis and physical-chemical research of 7-((3-thio-4-r-4h-1,2,4-triazole-5-yl)methyl)theophylline carbonyl derivatives - A. S. Gotsulia; P. S. Knyazevich; O. I. Panasenko; Ye. G. Knysh (Zaporožskij Medicinskij Žurnal)
Aim. To analyze the carbonyl derivatives of 7-((3-thio-4-R-4H-1,2,4-triazole-5-yl)methyl)theophylline their mother substance was synthesized and its interaction with α-haloketones series was carried out.